'Way more relevant and a little less theoretical': how teaching artists designed for online learning in a pandemic. Issue 4 (2nd October 2022) - Dahn, Maggie; Yankova, Nickolina; Peppler, Kylie; Sikkema, Scott; Lee, Jenny; Spilberg, Joseph
ABSTRACT: The move to remote learning in the wake of the COVID-19 pandemic presented design challenges for teaching and learning. Though research is emerging on teacher adaptation during the pandemic that documents challenges and the perspectives of stakeholders, the field is lacking close descriptive accounts that illustrate what classrooms looked and felt like. We followed teaching artists as adaptive experts who designed responsive and emotionally safe spaces for students during the transition to remote learning. Our exploratory study was guided by the following research questions: (1) How did teaching artists design for teaching and learning during the pandemic? (2) What can be learned from teaching artists in responding to extraordinary circumstances moving forward? We found that teaching artists designed for online learning through centering relationships and resourcefulness, providing emotional support, cultivating introspection and empathy, expanding what counted as arts practice, and including families. We end with implications for research and practice.